Sodium-Glucose Cotransporter-2 inhibitors utilization and outcomes in patients with chronic kidney disease at a tertiary centre - Kuan, Yee L; Abdul Halim AG, (Penerbit UKM, 2023)
Sodium-glucose cotransporter-2 (SGLT2) inhibitor is an antidiabetic agent with cardiac and renal protective properties. Its renal protective property is a result of the inhibition of tubular sodium reabsorption and reduction in the intraglomerular pressure. The use of SGLT2 inhibitor in chronic kidney disease (CKD) independent of diabetic status is emerging. However, the real-world data of SGLT2 inhibitor utilisation in CKD is limited. We conducted a descriptive study of patients with CKD, who were prescribed with SGLT2 inhibitor in our Nephrology Clinic. A total of 156 patients were initiated on SGLT2 inhibitor from 2017 to 2022. Among them, 58.3% were male, with a mean age of 61 + 13 years, and 86.5% had diabetes mellitus, with estimated mean glomerular filtration rate (eGFR) of 46.41 + 21.14 ml/min/1.73m2, and proteinuria of 2.22 + 2.62 g/day. A total of 85.9% of patients were on renin-angiotensin-system (RAS) blockers, whereby those who were not prescribed with RAS were mostly CKD stage 4. Among the non-diabetic patients, 81% had glomerulonephritis, half of which was IgA nephropathy, and 42.9% were on immunosuppressants. There was a significant retardation of eGFR decline over a six-month-duration after the initiation of SGLT2 inhibitor from -3.46 + 6.56 ml/ min/1.73m2 to -0.77 + 7.97 ml/min/1.73m2 (p=0.001). The retardation of eGFR decline was more pronounced in more advanced CKD stages. However, the proteinuria reduction was insignificant over a six-month-duration (-0.03 + 2.31 g/day). There were no adverse events reported. In conclusion, SGLT2 inhibitor retarded the eGFR decline with minimal proteinuria reduction in short-term. Nonetheless, long-term efficacy and safety data of SGLT2 inhibitor in local populations requires further evaluation.